ANALISIS WACANA TEKSTUAL DAN KONTEKSTUAL NASKAH DRAMA BERJUDUL SARAPAN TERAKHIR KARYA ANDRIAN EKA SAPUTRA - Indra Agustia; Dindin Muhammad Zainal Muhyi; Desti Fatin Fauziyyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Discourse is a complete form of language unit arranged in its entirety so that it becomes a single language unit that contains a theme. There are two types of discourse in drama scripts, namely textual discourse and contextual discourse. This research is a descriptive qualitative research because in this research it tries to collect data based on the literature that is used as analysis material. In textual discourse in grammatical relationships, there are 105 reference data which include personal, demonstrative and comparison references, 20 duplication data including nominal, verbal, phrasal and clauseal references. 19 discharge data and 8 coupling data. Furthermore, in the textual discourse of lexical relations, there are 25 repetition data including epizeukis, tautotes, anasphora and episphora. 19 synonymy data includes free morphemes with bound, words with words, words with phrases and phrases with phrases. 21 collocation data, 6 hyponymy data and 2 equivalence data. The researcher found 14 data that included interpretation including the principle of personal interpretation, 3 locational interpretation data, 6 temporal interpretation data, 3 analogy data related to the interpretation of differences in meaning in an utterance, then the researcher found 12 interference data marked by the speaker not explaining explicitly the meaning of his utterance. In this study associated with the Basic Competence 3.19. Analyzing the content and linguistics of dramas that are read or watched at the XI grade high school level then alternatively as LKPD.